Familial Ebstein Anomaly: Whole Exome Sequencing Identifies Novel Phenotype Associated With FLNA. (December 2017) - Mercer, Catherine L.; Andreoletti, Gaia; Carroll, Aisling; Salmon, Anthony P.; Temple, I. Karen; Ennis, Sarah
Abstract : Background—: Familial Ebstein anomaly is a rare form of congenital heart disease. We report 7 individuals among 2 generations of 1 family with Ebstein anomaly. This family was first reported in 1991 by Balaji et al in which family members were also reported to have a mild skeletal phenotype. The most likely mechanism of inheritance was concluded to be autosomal dominant. We sought to identify the genetic pathogenesis in this family using a next generation sequencing approach. Methods and Results—: Whole exome sequencing was performed in 2 cousins in this family using the Agilent SureSelect Human all Exon 51 Mb version 5 capture kit. Data were processed through an analytic in-house pipeline. Whole exome sequencing identified a missense mutation in FLNA (Filamin A), an actin-binding protein located at Xq28, mutations in which are associated with the skeletal phenotypes Frontometaphyseal dysplasia, Otopalatodigital, and Melnick–Needles syndrome, with X-linked periventricular nodular heterotopia and FG syndrome (Omim, 305450). Review of the phenotypes of those with the mutation in this family shows increased severity of the cardiac phenotype and associated skeletal features in affected males, consistent with X-linked inheritance. Conclusions—: Although congenital heart disease is reported in families with mutations in FLNA, this is the first report of individuals being affected by Ebstein anomaly because of a mutation in this gene and details the concurrent skeletal phenotype observed in this family. Abstract : Supplemental Digital Content is available in the text.